Monoclonal Antibodies Specific for a Conformationally Altered State of Fibrinogen - Zamarron, Concepcion; Ginsberg, Mark H; Plow, Edward F (Thrombosis and Haemostasis, 1990)
Four monoclonal antibodies were selected by their ability to discriminate surface-bound from soluble fibrinogen. These antibodies reacted with insolubilized fibrinogen but not other immobilized proteins and their reaction with surface-bound fibrinogen was not diminished by a 100-fold excess of sotuble fibrinogen. The antibodies reacted with the same or spatially proximal epitopes, and the recognized epitope(s) resided within the gamma chain segment of the D domain of fibrinogen. Fab fragments of the antibodies inhibited fibrin polymerization in a dose dependent manner, suggesting that the epitope(s) was also exposed by the conversion of fibrinogen to fibrin. These data indicate that adsorption of fibrinogen onto a surface induces conformational changes and that similar changes are also evoked when fibrinogen is converted into fibrin.